PECULIARITIES OF COMMUNICATION IN THE EDUCATIONAL SPHERE OF THE DIGITAL SOCIETY - Chenbai, N.; Herasymenko, S. (Proceedings of the National Aviation University Series Philosophy Cultural, 2025)
Inftroduction. Social media has become a distinctive environment for the socialization of modern youth, displacing traditional social institutions where communication once took place. This situation may potentially give rise to numerous societal problems in the future, prompting efforts to address them through a comprehensive reform of the educational system. Researchers have increasingly focused on the problem of communication, which has acquired a philosophical dimension and, accordingly, requires a deeper understanding of its essence and the identification of ways to resolve it. The aim of the study is to identify the specific features of communication and interaction in the educational sphere under conditions of digitalization. Research methods are the systemic and sociocultural approaches, the principle of historicism, and the methods of logical analysis and synthesis. Research results. The history of humanity demonstrates a direct correlation between the level of civilization and the duration of the educational process. In the digital age, a person must possess a conscious need for knowledge, on which the quality of life directly depends. Therefore, new tasks have arisen for educators. The cognitive activity of young people and their interest in learning depend on the teacher's ability to create the necessary conditions for effective communication during the educational process. For an educational institution to fulfill its mission, communication at all levels requires the use of various channels, methods, and means. Discussion. The digitalization of the educational process is an objective reality, which in our country is unfolding under challenging conditions. Educators had to quickly adapt and establish communication in a digital environment. For many, this proved to be a serious challenge. Researchers have increasingly begun to report a deepening of digital inequality. One cannot ignore the issue of students’ low motivation to pursue education. The success of communication—and consequently, the level of trust and acceptance of what the teacher conveys—also depends on the adherence to a common set of rules by all participants in the educational process. Conclusions. The problem of interaction and communication has gone beyond the scope of psychology and has acquired an interdisciplinary status. The educational community is making considerable efforts to demonstrate to the new generation of students the advantages of face-to-face communication. Addressing this issue will influence the qualitative development of human civilization in the future.